Breaking Down the Bilingual Cost in Speech Production. (25th October 2015) - Sadat, Jasmin; Martin, Clara D.; Magnuson, James S.; Alario, François‐Xavier; Costa, Albert
Abstract: Bilinguals have been shown to perform worse than monolinguals in a variety of verbal tasks. This study investigated this bilingual verbal cost in a large‐scale picture‐naming study conducted in Spanish. We explored how individual characteristics of the participants and the linguistic properties of the words being spoken influence this performance cost. In particular, we focused on the contributions of lexical frequency and phonological similarity across translations. The naming performance of Spanish‐Catalan bilinguals speaking in their dominant and non‐dominant language was compared to that of Spanish monolinguals. Single trial naming latencies were analyzed by means of linear mixed models accounting for individual effects at the participant and item level. While decreasing lexical frequency was shown to increase naming latencies in all groups, this variable by itself did not account for the bilingual cost. In turn, our results showed that the bilingual cost disappeared when naming words with high phonological similarity across translations. In short, our results show that frequency of use can play a role in the emergence of the bilingual cost, but that phonological similarity across translations should be regarded as one of the most important variables that determine the bilingual cost in speech production. Low phonological similarity across translations yields worse performance in bilinguals and promotes the bilingual cost in naming performance. The implications of our results for the effect of phonological similarity across translations within the bilingual speech production system are discussed.